Electrochemical Activity of Pure and Sn-Doped CeO2 Nanoparticles using Simple Chemical Precipitation Method - Anandalakshmi, K.; Venkatachalam, P.; Venugobal, J. (Journal of Scientific Research, 2023)
In the present work, pure and Sn-doped CeO2 nanoparticles (NPs) were synthesized by the chemical precipitation method calcined at 400 ºC for 4 h. Characterization of NPs was done through X-ray diffraction (XRD), UV-visible, photoluminescence (PL), Fourier transform infrared (FTIR) spectroscopy and high-resolution electron microscope (HRTEM) techniques. The XRD study revealed the crystalline nature, size, and structure of the prepared NPs. The HRTEM results illustrated cubic structure. The UV–visible and PL studies were used to measure the optical behaviors of CeO2 NPs. The UV-visible showed that the bandgap value of CeO2 NPs increased from 3.61 to 3.65 eV for different doping concentrations. The XRD study exhibited that the size of the CeO2 NPs reduced from 11.03 to 7.91 nm. From the TEM analysis, the average size of undoped and 10% Sn-doped CeO2 NPs was calculated as 9.3 and 7 nm, respectively. A cyclic voltammetric study confirmed that Sn-doped CeO2 exhibited a higher specific capacitance value than the pure CeO2. The chemical precipitation method observed excellent redox and oxidation behavior were observed for Sn-CeO2 NPs by the cyclic voltammetric study. The significant enhancement in the specific capacitance suggested that Sn-doped CeO2 is a promising material for supercapacitor applications.